Self-directed learning assessment practices in undergraduate health professions education: a systematic review - Tracey A.H. Taylor; Kyeorda Kemp; Misa Mi; Sarah Lerchenfeldt (Medical Education Online, 2023)
ABSTRACTPurpose The goal of this systematic review was to examine self-directed learning (SDL) assessment practices in undergraduate health professions education.Methods Seven electronic databases were searched (PubMed, Embase, PsycINFO, ERIC, CINAHL, Scopus, and Web of Science) to retrieve English-language articles published between 2015 and July of 2022, investigating assessment of SDL learning outcomes. Extracted data included the sample size, field of study, study design, SDL activity type, SDL assessment method, number of SDL assessments used, study quality, number of SDL components present utilising the framework the authors developed, and SDL activity outcomes. We also assessed relationships between SDL assessment method and number of SDL components, study quality, field of study, and study outcomes.Results Of the 141 studies included, the majority of study participants were medical (51.8%) or nursing (34.8%) students. The most common SDL assessment method used was internally-developed perception surveys (49.6%). When evaluating outcomes for SDL activities, most studies reported a positive or mixed/neutral outcome (58.2% and 34.8%, respectively). There was a statistically significant relationship between both number and type of assessments used, and study quality, with knowledge assessments (median-IQR 11.5) being associated with higher study quality (p < 0.001). Less than half (48.9%) of the studies used more than one assessment method to evaluate the effectiveness of SDL activities. Having more than one assessment (mean 9.49) was associated with higher quality study (p < 0.001).Conclusions The results of our systematic review suggest that SDL assessment practices within undergraduate health professions education vary greatly, as different aspects of SDL were leveraged and implemented by diverse groups of learners to meet different learning needs and professional accreditation requirements. Evidence-based best practices for the assessment of SDL across undergraduate healthcare professions education should include the use of multiple assessments, with direct and indirect measures, to more accurately assess student performance.